Transformation of Sports Practices in Pandemic and Post-pandemic Times - Esposito, Maurizio; Panzaru, Ciprian; Petroccia, Sara (Italian Sociological Review, 2023)
This study explores how sports activities and practices have transformed during the pandemic. These social phenomena have impacted society, organizations, interactions, and individuals (Luhmann, 2003). We conducted desk research and expert interviews in Italy and Romania. The data collected will demonstrate that the two countries represent different patterns of pandemic development. Italy was the most affected European country in the first wave of SARS-CoV-2 (hereafter COVID-19) in 2020. On the opposite side, Romania managed to control the situation well at the beginning of the pandemic. However, it was stronger affected in 2021, while Italy managed to control the situation much better. The desk research consisted of reviewing available official sources and literature (De Nunes, 2020; Pleyers, 2020) related to measures and policies taken to control the effects of Covid on sports activities. Qualitative data were obtained from expert interviews and a critical theoretical framework was applied to assess the countries’ restrictions. Our research aims to help to understand how social capabilities could be used to support sports activities in crisis times, as the COVID-19 pandemic was and is – first and foremost – a social phenomenon. Not surprisingly, COVID-19 has spread thanks to the multiple relationships – cultural, economic, political, etc. – that the world’s population has forged over a definitively global space, with differential impacts across places (Bailey et al., 2021) that pose sociology to face to understand these new complex scenarios, the main issues we had to face, the successes, the criticalities and the lessons learned.